2010
DOI: 10.1158/1535-7163.mct-09-1103
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel-Resistant Prostate Cancer Cells Remain Sensitive toS-Trityl-l-Cysteine–Mediated Eg5 Inhibition

Abstract: Castrate-resistant prostate cancer remains a major clinical challenge. Due to the toxicity profile of taxane-based chemotherapy and treatment failure in some patients, novel agents with improved efficacy to side effect profiles are urgently needed. Eg5, a member of the kinesin-5 family, controls the formation of the bipolar spindle during cell division, and suppressed Eg5 function leads to mitotic arrest. S-Trityl-Lcysteine (STLC) is a novel Eg5-specific small-molecule inhibitor. Here, we report the first stud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…4 In two recent studies involving Eg5 inhibition in prostate cancer, researchers found that docetaxel-resistant and non-resistant prostate cancer cell lines showed sensitivity to antisense oligonucleotide or S-trityl-Lcysteine. 16,17 In a previous study by some authors of the present study, the Eg5 inhibitor S(MeO)TLC was 10-fold more potent than the antisense oligonucleotide or S-trityl-Lcysteine for inhibition of cell proliferation and it was extremely specific toward Eg5. 18 In another recent study, S(MeO)TLC was shown to have potent anticancer activity in bladder cancer in vitro and in vivo.…”
supporting
confidence: 50%
“…4 In two recent studies involving Eg5 inhibition in prostate cancer, researchers found that docetaxel-resistant and non-resistant prostate cancer cell lines showed sensitivity to antisense oligonucleotide or S-trityl-Lcysteine. 16,17 In a previous study by some authors of the present study, the Eg5 inhibitor S(MeO)TLC was 10-fold more potent than the antisense oligonucleotide or S-trityl-Lcysteine for inhibition of cell proliferation and it was extremely specific toward Eg5. 18 In another recent study, S(MeO)TLC was shown to have potent anticancer activity in bladder cancer in vitro and in vivo.…”
supporting
confidence: 50%
“…34,35 These have revealed that docetaxel-resistant and non-resistant prostate cancer cell lines showed almost the same sensitivity to antisense oligonucleotide or STLC treatment. 34 In contrast to the antisense oligonucleotide and STLC used in those two studies, in our previous study, our target Eg5 inhibitor, S(MeO)TLC (20 mmol l 21 ), was at least 10-fold more potent for inhibition of cell proliferation, and was extremely specific to Eg5, without affecting other structurally and functionally related mitotic kinesins. 17 Furthermore, our current study confirmed that .…”
Section: Discussionmentioning
confidence: 99%
“…2). Kinesin motor proteins consist of a long coiled-coil stalk with a cargo-binding module at one end and globular motor domain (head) at the other (Wiltshire et al, 2010). Eg5 is a kinesin involved in bipolar spindle formation during mitosis.…”
Section: Motor Proteins: An Intracellular Accomplicementioning
confidence: 99%
“…Numerous Phase I and Phase II clinical trials have built a strong platform to bring Eg5 inhibitors to the clinical setting. One such inhibitor, S-trityl-L-cysteine (STLC), showed efficacy in Docetaxel-resistant prostate cancer cells and that STLC was not affected by P-glycoprotein (P-gp) upregulation (Wiltshire et al, 2010). A recent retrospective study identified Eg5 nuclear expression to be of clinical value as predictive marker of Docetaxel response in mCRPC patients, and a prognostic marker for hormone-naïve prostate cancer patients (Wissing et al, 2014).…”
Section: Motor Proteins: An Intracellular Accomplicementioning
confidence: 99%